2014
DOI: 10.1007/s00429-014-0927-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the AMPA receptor GluA1 subunit regulates memory load capacity

Abstract: Memory capacity (MC) refers to the number of elements one can maintain for a short retention interval. The molecular mechanisms underlying MC are unexplored. We have recently reported that mice as well as humans have a limited MC, which is reduced by hippocampal lesions. Here, we addressed the molecular mechanisms supporting MC. GluA1 AMPA-receptors (AMPA-R) mediate the majority of fast excitatory synaptic transmission in the brain and are critically involved in memory. Phosphorylation of GluA1 at serine resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 49 publications
7
40
0
Order By: Relevance
“…Additionally, in neurons, [Ca 2+ ] i and more specifically, influx of Ca 2+ through Ca V 1.2 channels, is considered to regulate Ca V 1.2 channel trafficking and endocytosis to tune excitability there (Green et al, 2007;Hall et al, 2013). Furthermore, phosphorylation of the AMPAR subunit GluA1 at Ser 845 by PKA and/or calcium/calmodulin-dependent protein kinase II, or PKC at Ser 831 , promotes plasma membrane insertion of the receptors, facilitating long-term potentiation by increasing channel P o and homeostatic scaling up (Makino et al, 2011;Diering et al, 2016;Olivito et al, 2016). Conversely, dephosphorylation by calcineurin leads to receptor internalization, long-term depression and homeostatic scaling down (Lee et al, 1998).…”
Section: Channel Currents Are Increased By Iso In Adult Ventricular Mmentioning
confidence: 99%
“…Additionally, in neurons, [Ca 2+ ] i and more specifically, influx of Ca 2+ through Ca V 1.2 channels, is considered to regulate Ca V 1.2 channel trafficking and endocytosis to tune excitability there (Green et al, 2007;Hall et al, 2013). Furthermore, phosphorylation of the AMPAR subunit GluA1 at Ser 845 by PKA and/or calcium/calmodulin-dependent protein kinase II, or PKC at Ser 831 , promotes plasma membrane insertion of the receptors, facilitating long-term potentiation by increasing channel P o and homeostatic scaling up (Makino et al, 2011;Diering et al, 2016;Olivito et al, 2016). Conversely, dephosphorylation by calcineurin leads to receptor internalization, long-term depression and homeostatic scaling down (Lee et al, 1998).…”
Section: Channel Currents Are Increased By Iso In Adult Ventricular Mmentioning
confidence: 99%
“…The role of the GluA1 subunit in learning and memory processes has been the most extensively investigated (Guntupalli et al., 2016; Hanley, 2008; Hsieh et al., 2006). The GluA1 subunit has several phosphorylation sites on its intracellular carboxy terminus (including Ser818, Ser831, and Ser845), and many of these sites are involved in the regulation of AMPARs at the synapse (Olivito et al., 2016). For example, phosphorylation at Ser831 and Ser845 regulates the conductivity of the ion channel and the translocation of the AMPAR to the surface membrane, respectively (Olivito et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The GluA1 subunit has several phosphorylation sites on its intracellular carboxy terminus (including Ser818, Ser831, and Ser845), and many of these sites are involved in the regulation of AMPARs at the synapse (Olivito et al., 2016). For example, phosphorylation at Ser831 and Ser845 regulates the conductivity of the ion channel and the translocation of the AMPAR to the surface membrane, respectively (Olivito et al., 2016). In an interesting manner, recent studies revealed that GluA1‐dependent synaptic transmission is impaired in AD, although its involvement in memory and cognitive process in AD remains unknown (Hsieh et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…GluA1, one of the subunits of AMPA receptor and its intracellular phosphorylation sites (S845 and S831) play a key role in hippocampal activity-dependent synaptic trafficking of AMPA receptor, which is of vital importance for learning and memory343536. We determined the hippocampal post-synaptic membrane protein levels of GluA1, p-S845 and p-S831.…”
Section: Resultsmentioning
confidence: 99%